The clinical regimens and cell membrane camouflaged nanodrug delivery systems in hematologic malignancies treatment - Liu, Yuanyuan; Yu, Shanwu; Chen, Yixiang; Hu, Zhihong; Fan, Lingling; Liang, Gaofeng (Frontiers in Pharmacology, 2024)
Hematologic malignancies (HMs), also referred to as hematological or blood cancers, pose significant threats to patients as they impact the blood, bone marrow, and lymphatic system. Despite significant clinical strategies using chemotherapy, radiotherapy, stem cell transplantation, targeted molecular therapy, or immunotherapy, the five-year overall survival of patients with HMs is still low. Fortunately, recent studies demonstrate that the nanodrug delivery system holds the potential to address these challenges and foster effective anti-HMs with precise treatment. In particular, cell membrane camouflaged nanodrug offers enhanced drug targeting, reduced toxicity and side effects, and/or improved immune response to HMs. This review firstly introduces the merits and demerits of clinical strategies in HMs treatment, and then summarizes the types, advantages, and disadvantages of current nanocarriers helping drug delivery in HMs treatment. Furthermore, the types, functions, and mechanisms of cell membrane fragments that help nanodrugs specifically targeted to and accumulate in HM lesions are introduced in detail. Finally, suggestions are given about their clinical translation and future designs on the surface of nanodrugs with multiple functions to improve therapeutic efficiency for cancers.